The Role of Bhabinkamtibmas in Preventing Fraud Through the Door-to-Door System in Majalengka - Silaban, Benjamin (Police Studies Review, 2024)
The making of this research was based on the high number of fraud criminal activity in Majalengka Regency Police. The writer’s problem formulations are: (1) role of bhabinkamtibmas in order to prevents fraud through door to door system in Majalengka Regency Police’s territory, (2) factors which affect the role of bhabinkamtibas in preventing fraud at Majalengka Regency Police’s territory. The writer used some of the late research for the guidelines of this research. The analytic tools which were used are management factors and management elements, while the concepts were KUHP and bhabinkamtibmas concept. This research used qualitative approach and descriptive analytic method. The writer focused on the role of bhabinkamtibmas. The data gathering methods which used by the writer are observation, interview, and document study. The location of this research was at Majalengka Regency. The results of this research were showing that the implementation of bhabinkamtibmas role in order to prevents fraud criminal activity through door to door in Kuningan Regency Police territory still haven’t succeeded. Findings showed that: (1) the implementation of bhabinkamtibmas role was still not according to the proceddures (2) The lack of bhabinkamtibmas personnel and facilities. According to the results, the writer gave some advice to the Chief of Majalengka Regency Police to give training to bhabinkamtibmas personnel. The chief was also expected to fulfil the facilities. The use of reward and punishment system was also needed to motivate the personnel. Those things were advice so that the implementation of door to door system could be well.